Pomponazzi and the Limits of Rational Theology - Nauta, Lodi (Vivarium, 2025)
What is Pomponazzi’s main goal in the last three books of De fato, in which he discusses age-old conundrums such as the compatibility of free will with divine providence, the compatibility of God’s eternal ordinance with the contingency of the world, and predestination? Scholars have offered widely divergent interpretations. The present article suggests that these interpretations can be brought into agreement by underlining what can be regarded as the main goal of De fato, namely to admit that rational theology cannot solve these issues in any rationally satisfactory manner. To show this, the article examines Pomponazzi’s views on these topics, suggesting that even when he discusses these issues “in accordance to evangelical tradition,” Pomponazzi still feels the pull towards determinism and to the idea that God acts necessarily according to the providential order established from eternity, rolling on ineluctably.